Characterization of oil palm (Elaeis guineensis Jacq.) empty fruit bunch fibre filled polybutylene succinate and tapioca starch biocomposites - Shafi, Ayu Rafiqah (2021)
In Malaysia, the production of biodegradable food packaging is not well established. Biodegradable polymers only were used in high-end products such as in medical instruments. This is due to the high cost of the raw materials caused industries are not interested to invest in the development of biodegradable food packaging. The major challenges for the development of biodegradable polymer as food packaging are the shortcomings related to brittleness and processability. In meantime, this research was come out with an alternative to replace conventional plastic and overcome the drawbacks of the biodegradable polymer by substitute a certain percentage of polymer with tapioca starch and natural fibre from oil palm. EFB fibre was added at 10 to 50wt% fibre loading. The percentage of water absorption of the samples increased maximum by 10.15% for 50wt% fibre loading and reached the equilibrium of absorption on day 8. The same trends were observed for water vapour permeability as the reading was increased as the EFB fibre loading increased. It was incredible to note that increasing the EFB fibre up to 20 wt.% and 30 wt.%, showed an increase in tensile strength from 14.27MPa to 16.16MPa and tensile modulus from 2965.81MPa to 3177.19MPa. The flexural strength was increased from 17.15MPa to 35.16MPa. However, the thermal stability of the composites decreased by 12.65°C as the fibre loading increased. The composites with 20-30 wt.% of fibre loading exhibited good physical and mechanical properties, respectively. Increasing trends in the performance of tensile strength and flexural properties were shown for the glycerol loadings up to 10 wt% by 45% and 31.25% respectively. The addition of glycerol in the composite from 7.5-15% significantly improves the flexibility of the composite as the elongation at break increase from 6.12% to 14.21%. Besides, thermal stability for composite with 10.wt% glycerol loading shows the highest thermal stability. This is due to better interfacial bonding and interaction between PBS, starch and fibre compounding. In rheological testing was showed the viscosity for all fibre loading in the composite was reduced as an increase in shear rate. The composites showed a shear-thinning behaviour thus, showed a non- Newtonian behaviour. Due to calendaring machine capacity and limitation, 20 wt.% of EFB fibre loading and 10 wt.% glycerol content were chosen as a final formulation. Two technique of thermoforming process were evaluated to thermoform the composite into a food packaging tray. The hot press technique was showed higher tensile strength compare with the vacuum forming method. In terms of strength, this development of food packaging is competitive with the current food packaging. Hence, the development of fully biodegradable food packaging is important in the effort to address the ongoing environmental problems and gradually substitute the widely used conventional packaging materials.